Boer War Tribute Medals - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2011)
When the soldiers of Great Britain and the Empire came home after serving in the Anglo-Boer War of 1899-1902 some of the places to which they returned, their regiments and other bodies chose to reward them with unofficial medals which were usually presented at a formal function held in their honour. This book is about the history of these medals and includes the unofficial medals presented to the defenders of Kimberley and O'kiep.